Development of a piglet model for cerebrovascular autoregulation assessment with altered PaCO2 - Sofie Dietvorst; Veerle Desloovere; Geert Meyfroidt; Bart Depreitere (Brain and Spine)
Introduction: Cerebrovascular autoregulation (CA) capacity can be impaired in the aftermath of acute brain injuries. Altered physiological states, such as hypo- and hypercapnia, affect CA. Although these effects have been demonstrated in several animal experiments, the exact effect of PaCO₂ on the plateau of cerebral blood flow (CBF) across the spectrum of arterial blood pressures has not been fully disclosed. Research question: The aim was to explore pial vasodynamics in response to changing PaCO₂ in a porcine cranial window model, as preparation for an experimental setup in which the CBF plateau position is investigated under different PaCO₂ conditions. Material and methods: Five piglets were brought under anesthesia, intubated, ventilated and instrumented with a cranial window through which pial arteriolar diameters could be microscopically observed. By changing ventilation to either hyper- or hypoventilation we were able to investigate a range of PaCO2 from 25 till 90 mmHg. Results: Altering the respiratory rate to manipulate PaCO₂ by ventilation appeared to be feasible and reliable. Discussion and conclusion: We found that ETCO₂ reliably represents PaCO₂ in our model. Pial arteriolar diameter changes followed the direction of PaCO₂ changes, but the effect of PaCO₂ on the diameters was not linear. Only in the hypercapnia setting did we observe a clear and consistent vasodilation of the pial arterioles.